Clinical and Radiographic Response of Extramedullary Leukemia in Patients Treated With Gemtuzumab Ozogamicin. Issue 3 (April 2019) - McNeil, Michael J.; Parisi, Marguerite T.; Hijiya, Nobuko; Meshinchi, Soheil; Cooper, Todd; Tarlock, Katherine
Abstract : Extramedullary leukemia (EML) is common in pediatric acute leukemia and can present at diagnosis or relapse. CD33 is detected on the surface of myeloid blasts in many patients with acute myelogenous leukemia and is the target of the antibody drug conjugate gemtuzumab ozogamicin (GO). Here we present 2 patients with CD33 + EML treated with GO. They achieved significant response, with reduction of EML on both clinical and radiographic exams, specifically 18 fluorine fluorodeoxyglucose positron emission tomography/computed tomography, demonstrating potential for targeted therapy with GO as a means of treating EML in patients with CD33 + leukemia and the utility of 18 fluorine fluorodeoxyglucose positron emission tomography/computed tomography monitoring in EML.